Результаты исследования по выбору и обоснованию параметров перспективного промышленного ГТД в диапазоне мощностей 10…12 МВт - Коняхин, В. И.; Рябов, А. А.; Герасименко, Д. А. (Eastern-European Journal of Enterprise Technologies, 2009)
The issues related to a selection of parameters for a current industrial engine, effects of thermodynamic cycle values on the engine appearance are under discussion. The analysis of technical characteristics of the existing industrial GTEs ranged from10 to 12 MW of power has been made. This publication describes the result of calculations performed on determining an effect of the engine component parameters on the engine effective efficiency.